Beauty Perception in Watching Skintific Skincare Product Content on Tik-Tok - Zahra, Meutia; Puspasari, Cindenia; Mardhiah, Ainol; Subhani, Subhani; Anismar, Anismar (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2024)
The development of technology and social media, particularly TikTok, has grown significantly as a promotional tool that provides information without high costs, requires minimal effort, and can be done in a short amount of time. The beauty industry leverages TikTok as a promotional medium through content featuring women with smooth and beautiful faces. This study uses the AISAS Model as the theoretical foundation to guide the collection of relevant and appropriate data for the research. This study aims to understand the perception of beauty in watching Skintific skincare product content on TikTok. Using a quantitative research method, this study is based on observation, questionnaire distribution, and documentation. The population in this study comprises Communication Science students at Universitas Malikussaleh from the 2020-2023 cohorts, totaling 984 individuals. The sample in this study is 91 respondents. The validity test results show that all the statements in this study have a value greater than the critical value (rtable) of 0.206. The normality test results indicate an Asymp. A sig value of 0.065, which is greater than the significance level of 0.05, suggests that the data is normally distributed. The coefficient of determination (R2) test results in an R Square value of 0.327. This indicates that there is a perception of beauty effect among respondents after watching Skintific skincare product content on TikTok.